An investigation into jet assisted submarine cable burial ploughs - Knight, Craig S. (Cranfield University, 2005)
Fibre optic telecommunication cables laid across the seaoor are buried in shallow water depth (<2000m) for protection against hazards arising from commercial shing and shipping activity. The cables are buried in a trench created by a sea plough, often jet assisted and towed from a ship, or by a ROV with jet legs straddling the cable and uidising the soil around it. Recent trends in the industry require more versatile burial tools, so a sound understanding of their fundamental mechanics is required to enable their optimun design and performance. The aim of this research program was to study the mechanics of force reduction on jet assisted cable burial tools. The experimental program consisted of two stages, both conducted in controlled submerged conditions. The rst studied the effects of jet parameters, tool rake angle and pore pressure on tool force reduction. The second stage studied the action of a single horizontal buried jet on the surrounding soil, in which the rst series of experiments studied a static jet nozzle in sand and clay, and the second a dynamic jet nozzle. The flow rate or nozzle Velocity was varied in each respectively. The rst stage showed force reduction was caused by the reduced soil stress on the tool face in areas intersecting uidised sand. The larger the uidised area (FA), or the lower its intersection, the greater the force reduction. Evenly spaced nozzles gave greater FA coverage of the tool face. Interaction between jet and rake angle and force was complex, but upward angled jets and forward raked tools gave least force reduction. Results of the second stage showed cavity formation in sands characterised by shear erosion whereas in clay by pressure fracturing. The cavity size in sands was directly proportional to jet momentum ux and inversely proportional to tool Velocity. Mathematical models were developed from each stage, the rst to simulate tool force reduction created by the jets, given knowledge of the FA, and the second to simulate the FA created by a single jet. The second over predicted cavity length by a average of 7% over the range of tool velocities tested. The combined models over predicted tool force, and suggested reasons for the discrepancies are given. Further research is required to rene the model and provide a useful tool for the design and operation of jet assisted cable burial tools in saturated sands.